FAKTOR-FAKTOR INTERNAL RESILIENSI PENYANDANG DISABILITAS BARU KORBAN BENCANA GEMPA BUMI DI PROVINSI DIY - Hanjarwati, Astri (UIN Sunan Kalijaga Yogyakarta, 2023)
This article discusses the internal factors of resilience for people with new disabilities who are victims of the earthquake disaster. This research was conducted using a quantitative and qualitative approach (mix method). There were 124 respondents who were involved in this study consisting of people with new disabilities and their families who came from six sub-districts in Bantul Regency. Data was collected by conducting surveys of new persons with disabilities and interviewing families of persons with disabilities. The data that has been collected is then analyzed using SPSS analysis for survey results and coding for interview results. The results of the study show that the internal factors that influence people with disabilities to become resilient are adaptability, problem-solving skills, high optimism, good relationship building skills, and skills to contribute to society. Keywords: Internal factor, earthquakes, people with new disabilities, resilience.